2020
DOI: 10.1242/jcs.232488
|View full text |Cite
|
Sign up to set email alerts
|

Cell invasion by intracellular parasites – the many roads to infection

Abstract: Intracellular parasites from the genera Toxoplasma, Plasmodium, Trypanosoma, Leishmania and from the phylum Microsporidia are, respectively, the causative agents of toxoplasmosis, malaria, Chagas disease, leishmaniasis and microsporidiosis, illnesses that kill millions of people around the globe. Crossing the host cell plasma membrane (PM) is an obstacle these parasites must overcome to establish themselves intracellularly and so cause diseases. The mechanisms of cell invasion are quite diverse and include (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 235 publications
0
21
0
1
Order By: Relevance
“…Inside the parasite, the cytosolic domain of AMA1 binds to a parasite actin-myosin motor to allow parasite moving toward the parasitophorous vacuole in process of formation (reviewed by Horta et al, 2020). This junction allows the parasite entry and the formation of a parasitophorous vacuole that is protective to the parasite because its composition exclude proteins from the host endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Inside the parasite, the cytosolic domain of AMA1 binds to a parasite actin-myosin motor to allow parasite moving toward the parasitophorous vacuole in process of formation (reviewed by Horta et al, 2020). This junction allows the parasite entry and the formation of a parasitophorous vacuole that is protective to the parasite because its composition exclude proteins from the host endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…They show various aspects of the structural organization of the different developmental stages of T. gondii [ 13 – 23 ]. Our analysis also considered the contributions of several other groups that have provided relevant contributions to the field [ 24 26 ]. All animations and images were produced using software such as 3D Max (Autodesk Inc., San Rafael, CA.…”
Section: Available Materialsmentioning
confidence: 99%
“…Of note, as presented in table 1, caveolae are not exclusive entry gates for these pathogens, who "hijack" other cellular entry pathways [for an update on bacterial manipulation of clathrin see (Latomanski and Newton, 2019), for endocytotic mechanisms used by viruses, (Slonska et al, 2016)and for parasites (Horta et al, 2020)]. Furthermore, lipids enriched in caveolae could play a part in virus entry (Ewers et al, 2010)and virus replication (Favard et al, 2019), but can be found elsewhere in the plasma membrane.…”
Section: Parasitesmentioning
confidence: 99%